Optimalisasi Kelas Ibu Hamil melalui Pendekatan Kesehatan Mental Berbasis Komunitas - Nurvitasari, Rahsunji Intan (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2025)
Maternal mental health is a crucial factor influencing the well-being of mothers and fetal development. Mental health screening in primary care is rarely conducted, leading to undetected issues. This community service aimed to enhance pregnant women’s knowledge of mental health while conducting screening using the Depression Anxiety and Stress Scale (DASS-21). The program involved 45 pregnant women in the working areas of Bantul I and Bantul II Community Health Centers. Methods included education, interactive Q&A sessions, and completion of the DASS-21 questionnaire. Results indicated that most participants were in the normal category across all age groups. However, moderate cases were found in women aged >35 years (7.7%), mild cases in working participants (11.1%), mild cases in the second trimester (7.7%), and moderate cases in the third trimester (4.5%). Participants actively engaged in discussions, shared experiences, and informally formed peer support groups. This program demonstrated that education combined with screening can raise awareness and foster social support networks among pregnant women.